Interactions in a high immigration context - Aycinena, Diego (2024)
Sudden massive migration influxes have been a new driving force of migration increases in recent decades. These types of migration flows present potential challenges to social and economic integration. In this paper we study socioeconomic integration using controlled laboratory experiments in a context of massive inflow of Venezuelan migrants in Peru, where the share of Venezuelan immigrants in the country’s population increased from almost zero in 2016 to 2.5 percent in 2019. Using adult (non-student) native-born Peruvians and Venezuelan immigrants as subjects, we conducted homogeneous (same nationality) and mixed (different nationality) experimental sessions in Lima, to examine interactions that require cooperation, coordination, trust, and reciprocity to achieve a Pareto efficient outcome. We find no evidence of in-group versus out-group (based on nationality) difference in those measures of pro-social behavior. Within this context, we also find no differentials in normative or empirical expectations in behavior of non-nationals relative to those of nationals, and only small to moderate implicit bias. This lack of differential treatment is suggestive of short-run economic integration between immigrants and natives, in a challenging context of massive influxes of migrants.